LncRNA GAS5 represses stemness and malignancy of gliomas via elevating the SPACA6-miR-125a/let-7e Axis - Wu, Shuang; Ren, Kaixi; Zhao, Jing; Li, Juan; Jia, Bo; Wu, Xiuquan; Dou, Yanan; Fei, Xiaowei; Huan, Yu; He, Xin; Wang, Tingting; Lv, Weihao; et al. (Frontiers in Oncology, 2022)
Glioblastoma (GBM) is a highly invasive neurological malignancy with poor prognosis. LncRNA-GAS5 (growth arrest-specific transcript 5) has been recognized as a tumor suppressor involved in multiple cancers. In this study, we explore the clinical significance, biological function, and underlying mechanism of GAS5 in GBM. We show that lncRNA-GAS5 was decreased in high-grade glioma tissues and cells and the decrease of GAS5 might associate with poor prognosis. GAS5 overexpression lowered cell viability, suppressed the migration and invasion of GBM cells, and impaired the stemness and proliferation of glioma stem cells (GSCs). We further proved that GAS5 restrained the viability of glioma cells through miR-let-7e and miR-125a via protecting SPACA6 from degradation. Moreover, GAS5 played the role of antioncogene in GBM with the combined involvement of let-7e and miR-125a in both vivo and vitro and these two miRNAs could block IL-6/STAT3 pathways in tumor tissues extracted from the xenograft model. Taken together, our study provide evidence for an important role of GAS5 in GBM through affecting the proliferation and migration of GSCs, providing a new potential prognostic biomarker and treatment strategy for GBM.